Upadacitinib in the treatment of SAPHO syndrome: a case report - Yang, Yanran; Sun, Zhanxue; Ge, Yongpeng (Frontiers in Immunology, 2025)
Synovitis, acne, pustulosis, hyperostosis, and osteitis (SAPHO) syndrome, a rare autoinflammatory disease, is usually defined by musculoskeletal symptoms and cutaneous manifestations. Cutaneous manifestations include palmoplantar pustulosis or severe acne, which are generally accompanied by osteitis and hyperostosis, and are the hallmark of SAPHO syndrome. Genetic, immune, and microbial factors are involved in the pathophysiology of the SAPHO. Small-molecule targeted therapies and biologic agents have transformed the treatment of inflammatory disorders. Upadacitinib, with efficacy in cytokine-related disorders, represents a therapeutic candidate for SAPHO syndrome. Here we report a patient with a 20-year history of pustular palmoplantar psoriasis (PPP) who developed progressive inflammatory arthralgia over the past decade. Radiographic and scintigraphic evaluations showed distinct sternocostoclavicular hyperostosis and osteitis, confirming a diagnosis of SAPHO syndrome. Conventional therapies, including nonsteroidal anti-inflammatory drugs (NSAIDs), disease-modifying antirheumatic drugs (DMARDs), and topical agents, failed to improve cutaneous or articular symptoms. After ineffective treatment with secukinumab (an IL-17A inhibitor), transitioning to upadacitinib (a selective JAK1 inhibitor) improved pustular lesions and reduced joint pain and inflammation, demonstrating clinical improvement. This case illustrates the effectiveness of upadacitinib, a selective JAK1 inhibitor, for the rapid resolution of cutaneous and articular symptoms of SAPHO syndrome following unsuccessful IL-17A inhibition, offering valuable insights for management of refractory SAPHO syndrome.